Pengaruh Keadilan Distributif, Keadilan Prosedural, Keadilan Interaksional, Persepsi Nilai, Terhadap Kepuasan dan Respon Positif Pelanggan Superindo Bojonegoro - Dwi Irnawati; Reza Anggapratama (Universitas Batanghari Jambi, 2023)
Service is the most important thing that customers need to be satisfied. If the customer is satisfied then the customer will give a positive response to the company, otherwise if the customer is not satisfied then the customer will give a negative response to the company. The purpose of this study is to empirically examine the effect of Distributive Justice, Procedural Justice, Interactional Justice and Value Perception on satisfaction and its effect on positive response by Superindo Bojonegoro customers. In this study, primary data were used with survey and questionnaire methods. In this study, 241 Superindo customers in Bojonegoro. This study used endogenous variables namely perceived value and fairness, and exogenous variables namely satisfaction, Customer Citizenship Behavior (CCB), and repeat purchase intent. The processed PLS 7.0 curve shows that value perception has a clear positive effect on CCB and customer satisfaction, and the fairness dimension has a clear positive effect on satisfaction, in addition satisfaction has a positive effect on CCB and repeat purchase intent. These results explain that satisfaction is strongly influenced by the company's services, including corporate fairness and perceived value of customers.